Enhancing Community Skills in Processing Yellow Pumpkin (Cucurbita moschata) as a Food Product for Tourists in the Ciwaluh Ecotourism Village - Sulistyawati, Eko Yuliastuti Endah; Ulfah, Mutiara; Susilo, Adhi; Hakiki, Dini Nur; Maulida, Iffana Dani (JAKADIMAS (Jurnal Karya Pengabdian Masyarakat), 2024)
Bogor Regency has vast and diverse ecotourism potential. One ecotourism in the Bogor Regency area is Ciwaluh Village, Wates Jaya Village, Cigombong District, Bogor Regency. This village produces yellow pumpkins that need to be optimally processed to attract tourists. In improving the skills of ecotourism cadres, training is carried out to enhance skills in processing yellow pumpkins (Cucurbita moschata) into snacks. The methods used in this training were surveys, identification of snack characteristics, demonstrations, and snack processing practices. The training provided is to improve skills in processing yellow pumpkin into various snacks. Based on the results of the pretest and posttest before and after the training for ecotourism cadres in Ciwaluh Village, it was found that skills in processing types of snacks increased by 66.67%. The skill improvement in processing various yellow pumpkin snacks for cadres can still be improved, considering that the variety of yellow pumpkin snacks is still growing in line with the research of yellow pumpkin’s product still being carried out